NORMAL ELEMENT ON IDENTIFY PROPERTIES - Titi Udjiani; Solikhin Zaki; Suryoto Suryoto; Harjito Harjito (Journal of Fundamental Mathematics and Applications (JFMA), 2018)
One type of element in the ring with involution is normal element. Their main properties is commutative with their image by involution in ring. Group invers  of element in   ring  is  always commutative with element   which is commutative  with itself. In this paper, properties of normal element in ring with involution  which also have generalized  Moore Penrose invers  are constructed by using commutative property of  group invers  in  ring.